Assessing the Open Market Sale (OMS) as an Urban Food Safety Net in Bangladesh: Policy and Practice Gaps - Maruf Hasan Rumi; Md. Nure Alam (Journal of Asian Social Science Research, 2025)
Abstract Public food distribution programmes are central to social protection efforts, yet their performance often falls short of their stated goals. This study evaluates the service quality of the Open Market Sale (OMS) programme, which provides subsidised food grains to low-income urban residents, and examines how institutional and political factors shape its outcomes. Using a qualitative design informed by critical realism, the research draws on 20 in-depth interviews with purposefully selected beneficiaries and 10 key informant interviews with programme administrators, dealers and community leaders, complemented by documentary analysis of policy and evaluation reports. The findings show that, although OMS offers short-term price relief, its service quality is undermined by long queues, uncertain access, inadequate ration sizes, poor food quality and weak responsiveness to complaints. Targeting errors, institutional capacity gaps, chronic underfunding and pervasive corruption, including political influence over dealer selection and outlet locations, further distort benefit distribution and generate significant leakages and losses along the supply chain. The study concludes that the programme only partially protects food-insecure households and requires substantial reform in both design and implementation. Empirically, it contributes fine-grained evidence on how front-line practices and local power relations shape the performance of food-based safety nets. Policy implications include the need to strengthen data-driven targeting, increase transparency and accountability, invest in storage and monitoring systems, and integrate OMS within a broader, more coherent social protection strategy.